PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CORPORATE REPUTATION, WORD OF MOUTH DAN CUSTOMER TRUST (STUDI DI PT PETROKIMIA GRESIK) - Farisi, Jawad; Premananto, Gancar Candra (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
At the end of 2019, a global pandemic began to hit the whole world, including Indonesia. This seems to have influenced the consumer confidence index. Consumer confidence in current economic conditions has weakened due to weakening incomes and reduced job availability. The existence of problems related to the decrease in the level of consumer confidence will be very detrimental to the company if the solution is not immediately considered. The purpose of this study was to examine and analyze the effect of corporate social responsibility on corporate reputation, word of mouth and customer trust as well as the effect of corporate reputation and word of mouth on customer trust. This research applies a quantitative approach with the type of research applied is causal research. The population in this study were 344 consumers of PT Petrokimia Gresik (PG), while the sample used in the study was 185 people.Data analysis in this study uses inferential statistics, which is an analysis aimed at proving the hypothesis using structural equation modeling - AMOS. The results of this study found that corporate social responsibilityprovides a significant effect on corporate reputation, word of mouth and consumer trust. Then corporate reputation and word of mouth are also proven to have a significant effect on consumer trust.